Surviving Unemployment without State Support: Unemployment and Household Formation in South Africa - Stephan Klasen; Ingrid Woolard (Institute for the Study of Labor (IZA), 2000)
High unemployment in many OECD countries is often attributed, at least in part, to the generosity and long duration of unemployment compensation. It is therefore instructive to examine a country where high unemployment exists despite the near complete absence of an unemployment insurance system. In South Africa unemployment stood at 23% in 1997 and the unemployed have no unemployment insurance nor informal sector activities to fall back on. This paper examines how the unemployed are able to get access to resources without support from unemployment compensation. Analysing a household survey from 1995, we find that the household formation response of the unemployed is the critical way in which they assure access to resources. In particular, unemployment delays the setting up of an individual household of young people, in some cases by decades. It also leads to the dissolution of existing households and a return of constituent members to parents and other relatives and friends. Access to state transfers (in particular, non- contributory old age pensions) increases the likelihood of attracting unemployed persons to a household. Some unemployed do not benefit from this safety net, and the presence of unemployed members pulls many households supporting them into poverty. We also show that the household formation responses draw some unemployed away from employment opportunities and thus lowers their employment prospects. The paper discusses the implications of these findings for debates about unemployment and social policy in South Africa and in OECD countries.
Keywords: J61; J23; O15; J12; 330; Unemployment; household formation; South Africa; incentive effects; Arbeitslosigkeit; Privater Haushalt; Selbsthilfe; Haushaltsökonomik; Armut; Südafrika